MORPHOGENESIS AND HISTOPATHOLOGY OF FRUIT GALLS INDUCED BY Pseudophacopteran sp. ON Alstonia scholaris - MANNA, SANJUKTA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Alstonia scholaris (Chatim Tree) invites attention of the researchers worldwide as these plants are seriously damaged by insect galls which affect its ornamental and medicinal value. Plant galls are pathologically developed cells, tissues and organs of plants which induced by influence of a parasitic organism, like viruses, bacteria, fungi, algae, nematodes, mites or insects. Hence an attempt has been made to study the histological and biochemical changes in fruit galls induced by Pseudophacopteran sp., a psylloid herbivores on Alstonia scholaris. The adult insect was yellowish in colour, winged and with bulging eyes. The nymph undergoes moulting to reach the adult stage inside the fruit chamber. Hyperplasia in the pericarp was very distinctly noticed. The pericarp proliferated to form a “covering gall”. Chlorophyll content in the gall tissue decreased. A steady increase of carbohydrate content in galled fruit was due to the manipulation of plant cell metabolism in galls. Increased phenolic content exerted oxidative stress in response to pathogen in the fruit cell lineages thus inhibited seed formation.